2004
DOI: 10.1117/12.568039
|View full text |Cite
|
Sign up to set email alerts
|

<title>Novel multilayered SERS substrates for trace chemical and biochemical analysis</title>

Abstract: We have developed and characterized novel multilayered metal film-based surface-enhanced Raman scattering (SERS) substrates capable of enhancing SERS signals over an order of magnitude compared to conventional single layer substrates. In addition to enhanced signal intensity, these multilayered metal film substrates also exhibit longer SERS active lifetimes, higher reproducibility and lower detection limits than single layer silver substrates. Multilayered metal film substrates were fabricated by repeated vapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Slides rotate during deposition to ensure a uniformly coated metal surface is produced. 38,89 Substrates were regenerated by depositing approximately 500nm of Au on the stripped Klarite surface. 1.9 Plasmon Data.…”
Section: Stripping Of Klarite Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…Slides rotate during deposition to ensure a uniformly coated metal surface is produced. 38,89 Substrates were regenerated by depositing approximately 500nm of Au on the stripped Klarite surface. 1.9 Plasmon Data.…”
Section: Stripping Of Klarite Surfacementioning
confidence: 99%
“…It is suggested that the reader look to several comprehensive reviews and interesting papers for a more complete discussion of SERS substrate fabrication techniques, applications, advantages and challenges. 1,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] One of the more common and easily achieved methods for the fabrication of SERS substrates is known as the drop and dry technique. Drop and dry techniques or Film over Nanosphere (FONS) offer some advantages as compared to other fabrication methods like ease of fabrication due to cheaper manufacturing materials, and often being lower cost in skill, time and overall materials as compared to some other more fabrication intensive techniques.…”
Section: Example Sers Substratesmentioning
confidence: 99%
“…The more sensitive substrate platforms generally have a 15% relative standard deviation (RSD; the measure of the reproducibility of an analysis) from substrate-to-substrate and SERS signal enhancements of 7 to 8 orders of magnitude. (60,61) Consequently, many researchers in academia, industry, and government have focused concerted efforts toward increasing the signal enhancement ability, reproducibility, and mass production manufacturing of substrates to increase the utility of this technique. (5,67) For the Army and first responders, such a substrate platform with increased sensitivity and reliability would be very advantageous for the detection and identification of unknowns.…”
mentioning
confidence: 99%
“…(48) Because of the many sensing advantages of SERS-based techniques, significant research efforts (defense, industrial and academic) have been directed toward fabricating "better" SERS substrates for SERS-based sensor platforms. (48)(49)(50)(51)(52)(53)(54)(55)(56)(57) Some of these SERS platforms are fabricated from colloids (58) , film over nanospheres (59)(60)(61)(62) , fiber optic bundles (3) , nanoparticles, (55,(63)(64)(65)(66) and lithographically (5) produced structures. The more sensitive substrate platforms generally have a 15% relative standard deviation (RSD; the measure of the reproducibility of an analysis) from substrate-to-substrate and SERS signal enhancements of 7 to 8 orders of magnitude.…”
mentioning
confidence: 99%
“…Some examples of SERS substrate fabrication include self-assembly through such techniques like drop and dry, directed or templated assembly, thin film growth, and nanolithography. It is suggested that the reader look to several comprehensive reviews and interesting papers for a more complete discussion of SERS substrate fabrication techniques, applications, advantages and challenges3,11,17,24,33,84,85,[108][109][110][111][112][113][114][115][116][117][118][119][120][121] .…”
mentioning
confidence: 99%